Representasi Kekerasan Seksual Terhadap Perempuan dalam Film Like and Share - Rizky Rahmayanti; Kheyene Molekandella Boer; Jaka Farih Agustian; Nurliah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study discusses the representation of sexual violence against women in the film Like and Share by Gina S. Noer, using the Charles Sanders Peirce semiotic model method. This film depicts the complexity of sexual violence, especially in the digital world, through a strong narrative and complex characters. The study was conducted with an in-depth analysis of symbols, objects, and interpretations of signs in the film, including sexual assault, intimidation, and the distribution of pornographic content without permission. The results of the analysis show how technology exacerbates sexual violence and the important role of media in building public awareness of this issue. This study contributes to understanding the representation of sexual violence in the media and the importance of privacy protection and digital ethics.